The Effects of NAM on the Symmetry of the Face and Maxillary Arch in Babies With Unilateral Cleft - de Souza, Tânia Mara; Batista, Sabrina Tailane; de Souza, Rodrigo Xavier Silveira; Rezende, Sérgio Edriane; Alessi, Mariana Sisto; Almeida, Tatiana Fernandes Araújo; Frazão, Diogo Campos [UNESP]; Pretti, Henrique; da Silva Freitas, Renato; Macari, Soraia (Wolters Kluwer, 2023)
The study aimed to evaluate the effect of nasoalveolar molding (NAM) therapy through reverse engineering, or its absence, to obtain symmetry of the face and maxillary arch. Twenty-six babies with unilateral cleft lip and palate received treatment with NAM, and 12 babies with unilateral cleft lip and palate without presurgical orthopedics (control group). Patients were molded and photographed in 2-stages: the first month of life (T1/pre) and after the use of NAM/before the cheiloplasty (T2/post). In the digital models, the analyses performed were arch perimeter, arch length, and labial frenulum angle. The photographs allowed us to analyze nasal width, mouth width, columella angle, and nostril area. The results demonstrated that there was an increase in arch perimeter and arch length in control and NAM groups in the T2 period in comparison to T1. Labial frenulum angle was reduced in the NAM group compared to the NAM-T1 and control-T2 periods. Treatment with NAM yielded a reduction in nasal width in the period of T2 compared with T1. Columella angle was enhanced after NAM use in T2 and, was different from control group. The nostril area was reduced in the NAM group in T2 compared with control group. Nasoalveolar molding therapy reduced the labial frenulum angle, contributing to a reduction in the extension of the cleft. The NAM protocol improved facial symmetry, mainly through nasal effects, whereas the absence of orthopedic therapy yielded a commitment to the face and maxillary arch symmetry.